Anterior Cervical Discectomy and Fusion in the Outpatient Ambulatory Surgery Setting: Analysis of 2000 Consecutive Cases. Issue 3 (10th December 2019) - McGirt, Matthew J; Rossi, Vincent; Peters, David; Dyer, Hunter; Coric, Domagoj; Asher, Anthony L; Pfortmiller, Deborah; Adamson, Tim
Abstract: BACKGROUND: In an effort to improve efficiency of care, ambulatory surgery centers (ASCs) have emerged as lower-cost options. Anterior cervical discectomy and fusion (ACDF) is one of the most prevalent spine surgeries performed and rarely requires overnight stays in the hospital, supporting its migration to the ASC. Recent analyses have called into question the safety of outpatient ACDF, potentially slowing its adoption. ASC-ACDF studies have largely been limited to small series, precluding an accurate assessment of safety. OBJECTIVE: To analyze 2000 ASC-ACDF cases, describe patient selection and perioperative protocol, and report associated safety profile. METHODS: A total of 2000 patients who underwent 1 to 3 level ACDF in a single ASC from 2006 to 2018 were included in this retrospective analysis. Patients were observed in a 4-h postanesthesia care unit (PACU) with a multimodal pain management regiment. Data were collected on patient demographics, comorbidities, operative details, and 30- and 90-d morbidity. RESULTS: Of the 2000 patients, 10 (0.5%) required transfer to an inpatient setting within the 4-h observation. Reasons for transfer included hematoma (2), pain control (2), cerebrospinal fluid leak (1), and medical complications (5). Six patients (0.3%) underwent reoperation within 30 d. All-cause 30-d readmission was 1.9%. CONCLUSION: An analysis of 2000 ACDF patients in an ASC setting with a standardized perioperative protocol demonstrates that surgical complications occur at a low rate (<1%) and can be appropriately diagnosed and managed in a 4-h PACU. In an effort to decrease healthcare costs, surgeons can safely perform ACDFs in an ASC utilizing patient selection criteria and perioperative management protocols similar to those reported here. Graphical Abstract: